Social Pedagogy in the World Today: An Analysis of the Academic, Training and Professional Perspectives - Janer-Hidalgo, Ángela; Ucar, Xavier (The British Journal of Social Work, 2023)
We present a study of social pedagogy from a comparative perspective with the aim of offering an international overview of the current status of social pedagogy in the world. The lack of a universal conceptual definition for the term causes epistemological confusion and inaccuracy and has led to the emergence of multiple polarised perspectives on the concept in different contexts. Our study analyses the current situation from the academic, training and professional viewpoints, with the aim of developing a series of indicators to construct an updated, global and integrated view of social pedagogy. Each of these three visions forms a phase of research and uses a specific methodology: the academic perspective (qualitative methodology with the Delphi method), the training perspective (quantitative methodology with a statistical analysis) and the professional perspective (qualitative methodology with semi-structured interviews). Based On the triangulation of all results in different phases, our principal findings define the main dimensions of social pedagogy: contextual, historical, epistemological, functional, professional, methodological, normative and ethical and political. It also confirms that it is possible to define a theoretical, transdisciplinary and international common ground on social pedagogy and describe the specific features characteristic of each context.
Keywords: academic perspective; comparative study; professional perspective; social pedagogy; training perspective; JCR